Benefits of task‐shifting HIV care to nurses in terms of health‐related quality of life in patients initiating antiretroviral therapy in rural district hospitals in Cameroon [Stratall Agence Nationale de Recherche sur le SIDA (ANRS) 12110/Ensemble pour une Solidarité Thérapeutique Hospitalière en Réseau (ESTHER) substudy]. Issue 5 (27th February 2015) - Suzan‐Monti, M; Blanche, J; Boyer, S; Kouanfack, C; Delaporte, E; Bonono, R‐C; Carrieri, PM; Protopopescu, C; Laurent, C; Spire, B; Stratall ANRS 12110/ESTHER Study Group
<x xml:space="preserve">Abstract</x> Objectives The World Health Organization (WHO) recommends task‐shifting HIV care to nurses in low‐resource settings with limited numbers of physicians. However, the effect of such task‐shifting on the health‐related quality of life (HRQL) of people living with HIV (PLHIV) has seldom been evaluated. We aimed to investigate the effect of task‐shifting HIV care to nurses on HRQL outcomes in PLHIV initiating antiretroviral therapy (ART) in rural district hospitals in Cameroon. Methods Outcomes in PLHIV were longitudinally collected in the 2006−2010 Stratall trial. PLHIV were followed up for 24 months by nurses and/or physicians. Six HRQL dimensions were assessed during face‐to‐face interviews using the WHO Quality of Life (WHOQOL)‐HIV BREF scale: physical health; psychological health; independence level; social relationships; environment; and spirituality/religion/personal beliefs. The degree of task‐shifting was estimated using a consultant ratio (i.e. the ratio of nurse‐led to physician‐led visits). The effect of task‐shifting and other potential correlates on HRQL dimensions was explored using a Heckman two‐stage approach based on linear mixed models to adjust for the potential bias caused by missing data in the outcomes. Results Of 1424 visits in 440 PLHIV (70.5% female; median age 36 years; median CD4 count 188 cells/μL at enrolment), 423 (29.7%) were task‐shifted to nurses. After multiple adjustment, task‐shifting was associated with higher HRQL level for four dimensions: physical health [coefficient 0.7; 95% confidence interval (CI) 0.1–1.2; P = 0.01], psychological health (coefficient 0.5; 95% CI 0.0–1.0; P = 0.05), independence level (coefficient 0.6; 95% CI 0.1–1.1; P = 0.01) and environment (coefficient 0.6; 95% CI 0.1–1.0; P = 0.02). Conclusions Task‐shifting HIV care to nurses benefits the HRQL of PLHIV. Together with the previously demonstrated comparable clinical effectiveness of physician‐based and nurse‐based models of HIV care, our results support the WHO recommendation for task‐shifting.